2022
DOI: 10.1038/s41598-022-10629-7
|View full text |Cite
|
Sign up to set email alerts
|

GC–MS and LC-TOF–MS profiles, toxicity, and macrophage-dependent in vitro anti-osteoporosis activity of Prunus africana (Hook f.) Kalkman Bark

Abstract: Osteoporosis affects millions of people worldwide. As such, this study assessed the macrophage-dependent in vitro anti-osteoporosis, phytochemical profile and hepatotoxicity effects in zebrafish larvae of the stem bark extracts of P. africana. Mouse bone marrow macrophages (BMM) cells were plated in 96-well plates and treated with P. africana methanolic bark extracts at concentrations of 0, 6.25, 12.5, 25, and 50 µg/ml for 24 h. The osteoclast tartrate-resistant acid phosphatase (TRAP) activity and cell viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…If we compare the diseases identified in this study with those reported by previous research, we can observe a great similarity with local populations using P. africana in other countries. Indeed, a number of ethnobotanical studies have found that not only local populations but also the scientific community are attracted to this species because of its effective active ingredients against benign prostatic hyperplasia and prostate hypertrophy (Abera 2014;Ibrahim et al 2016;Jared Misonge et al 2019;Qureshi et al 2009;Tugume et al 2016;Komakech and Kang 2019;Komakech et al 2020;Komakech et al 2022), an increasingly common problem in older men. Beyond the prostate, our ethnobotanical surveys showed that local people also use P. africana in the treatment of other diseases.…”
Section: Types Of Parts Used and Diseases Treated By P Africana Extractsmentioning
confidence: 99%
“…If we compare the diseases identified in this study with those reported by previous research, we can observe a great similarity with local populations using P. africana in other countries. Indeed, a number of ethnobotanical studies have found that not only local populations but also the scientific community are attracted to this species because of its effective active ingredients against benign prostatic hyperplasia and prostate hypertrophy (Abera 2014;Ibrahim et al 2016;Jared Misonge et al 2019;Qureshi et al 2009;Tugume et al 2016;Komakech and Kang 2019;Komakech et al 2020;Komakech et al 2022), an increasingly common problem in older men. Beyond the prostate, our ethnobotanical surveys showed that local people also use P. africana in the treatment of other diseases.…”
Section: Types Of Parts Used and Diseases Treated By P Africana Extractsmentioning
confidence: 99%